Posttraumatic Stress Disorder, Antidepressant Use, and Hemorrhagic Stroke in Young Men and Women: A 13-year Cohort Study - Gaffey, Allison E. (Stroke, 2020)
BACKGROUND AND PURPOSE: Antidepressants are commonly prescribed for posttraumatic stress disorder (PTSD) and may increase the risk of bleeding, including hemorrhagic stroke. METHODS: We prospectively examined independent effects of PTSD, selective serotonin and norepinephrine reuptake inhibitors [SSRI and SNRI] on the risk of incident hemorrhagic stroke in a nationwide sample of 1.1 million young and middle-aged Veterans. Time-varying multivariate Cox models were used to examine hemorrhagic stroke risk by PTSD status and use of SSRI or SNRI while adjusting for demographics, lifestyle factors, stroke and psychiatric comorbidities. Sensitivity analyses controlled for healthcare utilization. RESULTS: During 13 years of follow-up (2.14 years on average), 507 patients (12% women) suffered a hemorrhagic stroke. The overall incidence rate was 1.70 events per 10,000-person years. In unadjusted models, PTSD was associated with an 82% greater risk of new-onset hemorrhagic stroke (HR, 1.82; 95% CI, 1.48–2.24), SSRI use was associated with a greater than 2-fold risk (HR, 2.02; 95% CI, 1.66–2.57), and SNRI use was associated with a 52% greater risk (HR, 1.52; 95% CI, 1.08–2.16). In fully-adjusted models, effects of PTSD and SNRI were attenuated (aHR, 1.03; 95% CI, 0.81–1.34; aHR, 1.19; 95% CI, 0.83–1.71), but SSRI use remained associated with a 45% greater risk of hemorrhagic stroke (aHR, 1.45; 95% CI, 1.13–1.85). Hypertension, drug abuse, and alcohol abuse were also associated with increased stroke risk. Non-obesity and being non-Hispanic were protective factors. In sensitivity analyses, healthcare utilization was a small but significant predictor of stroke. CONCLUSIONS: In the largest known investigation of PTSD and antidepressant-associated risk for hemorrhagic stroke in young adults, use of SSRIs, but neither PTSD nor SNRIs were independently associated with incident stroke. SNRIs may be preferable for treating PTSD and comorbid conditions, although pursuing other modifiable risk factors and non-pharmacological treatments for PTSD also remains essential.